Translanguaging practice in teaching internship among pre-service teachers: An analysis study of translanguaging in Indonesian EFL classrooms - Ricky Fajar Adiputra; Alief Noor Farida; Vionita Iken Restiana (ELT Forum: Journal of English Language Teaching, 2025)
This study addresses the limited research on translanguaging practices among pre-service teachers within the Indonesian English as a Foreign Language (EFL) context, especially among pre-service teachers. It aims to analyze how these novice teachers employ translanguaging as a pedagogical tool during their teaching internships, focusing specifically on its resources, methods, and purposes. Utilizing a qualitative descriptive approach, this research examines five publicly available YouTube videos of pre-service teachers' practicums, guided by the analytical framework of Jeon et al. (2025). The findings reveal that pre-service teachers fluidly integrate linguistic resources with a range of non-linguistic aids such as gestures and visual media. They demonstrated methodological agility, moving beyond simple translation ('translative' methods) to more complex 'interwoven' practices that seamlessly combine multiple resources in a single instructional flow. Furthermore, translanguaging was found to serve four key pedagogical purposes: material (clarifying academic content), managerial (organizing classroom activities), skill-building (scaffolding language acquisition), and expressive (fostering student participation and confidence). The study concludes and provides empirical evidence that these pre-service teachers effectively implement translanguaging strategies, challenging the notion of a significant theory-practice gap. Their performance suggests that their professional training is successfully equipping them to leverage students' full linguistic repertoires to create dynamic, inclusive, and effective learning environments.